RANCANGAN BUKU PENGAYAAN PENGETAHUAN "KAJIAN FISIS LUBANG HITAM" - Kustika Nisfatullaila Rohmah; Desnita, A. Handjoko Permana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This research aims to develop knowledge enrichment decent books, can motivate students and increase knowledge about the physics in astronomical phenomena, especially on the Black Hole. Discussion of this book covers material high school physics class XII K.D. 3.9 of Electromagnetic Radiation and class materials XI K.D. 3.2 Newton's law of gravity. The method used is research and development, which refers to the formulation of Dick & Carey has been developed by Atwi Supaman known as the Development Model of Instructional Design. Procedure development of knowledge-enrichment book consists of nine stages. Feasibility tests have been conducted by subject matter experts and learning experts with the achievement of 86% with the interpretation of "very good". Thus we can conclude the design of book knowledge enrichment "Physical Study Black Holes" worth as book knowledge enrichment. Keywords: book knowledge enrichment, electromagnetic radiation, Newton's laws of gravity, black holes